The Influence of Implementing the Merdeka Curriculum Learning System on Student Learning Outcomes - Pujiati, Asri; Firman, Muhammad; Helmi, M. Bahrul; Yulistiana, Arini Wigita; Apuanor, Apuanor (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study analyzes the effect of Merdeka Curriculum implementation on student learning outcomes, particularly at the secondary education level. The Merdeka Curriculum, introduced in 2022, aims to provide flexibility and freedom in the learning process, with an emphasis on project-based approaches and holistic development of student competencies. This study uses a qualitative method with data collection through questionnaires distributed to teachers and students at MTsN 1 Kotim. The results showed that the implementation of Merdeka Curriculum increased students' engagement, motivation, and learning achievement. In addition, teachers are required to be more creative in designing fun learning methods. However, challenges such as limited resources, student workload, and adaptation to curriculum changes are still obstacles. This study concludes that Merdeka Curriculum has great potential to improve the quality of education in Indonesia, with a note that it needs support in the form of teacher training, supporting facilities, and continuous evaluation.